Assessing sex‐related chick provisioning in greater flamingo Phoenicopterus roseus parents using capture–recapture models. (21st October 2013) - Rendón, Miguel A.; Garrido, Araceli; Rendón‐Martos, Manuel; Ramírez, José M.; Amat, Juan A.; Roulin, Alexandre
Summary In sexually dimorphic species, the parental effort of the smaller sex may be reduced due to competitive exclusion in the feeding areas by the larger sex or physiological constraints. However, to determine gender effects on provisioning patterns, other intrinsic and extrinsic factors affecting parental effort should be accounted for. Greater flamingos (Phoenicopterus roseus) exhibit sexual size dimorphism. In Fuente de Piedra colony, the lake dries out almost completely during the breeding season and both parents commute between breeding and foraging sites >130 km away during the chick‐rearing period. Applying multistate capture–recapture models to daily observations of marked parents, we determined the effects of sex, and their interactions with other intrinsic and extrinsic factors, on the probability of chick desertion and sojourn in the colony and feeding areas. Moreover, using stable isotopes in the secretions that parents produce to feed their chicks, we evaluated sex‐specific use of wetlands. The probability of chick attendance (complementary to chick desertion) was >0·98. Chick desertion was independent of parental sex, but decreased with parental age. Females stayed in the feeding areas for shorter periods [mean: 7·5 (95% CI: 6·0–9·4) days] than males [9·2 (7·3–11·8) days]. Isotopic signatures of secretions did not show sex differences in δ13C, but males' secretions were enriched in δ15N, suggesting they fed on prey of higher trophic levels than females. Both parents spent approximately 1 day in the colony, but females prolonged their mean stay when the lake dried out. Females also allocated more time to foraging in the flooded areas remaining in the colony, likely because they were energetically more stressed than males. The results indicate that sex‐specific provisioning behaviour in greater flamingo is related to differential effects of both intrinsic and extrinsic factors. Males seem forage less efficiently than females, whereas females' body condition seems to be lower after feeding the chick. Our methodology may be extended to species that feed on distant food sources and that do not visit their offspring daily, to elucidate patterns of chick‐provisioning behaviour.